2018
DOI: 10.1002/pmic.201700388
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Proteome and Ubiquitylome Reveals Unique Features of Lysosomal and Endocytic Pathways in Gefitinib‐Resistant Non‐Small Cell Lung Cancer Cells

Abstract: Non‐small cell lung cancer (NSCLC) patients carrying EGFR activating mutations treated with gefitinib, a tyrosine kinase inhibitor, will develop drug resistance. Ubiquitylation is one of major posttranslational modifications of proteins affecting the stability or function of proteins. However, the role of protein ubiquitylation in gefitinib resistance is poorly understood. To systematically identify the global change in protein expression and ubiquitylation during gefitinib resistance, a quantitative global pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
(29 reference statements)
3
15
0
Order By: Relevance
“…As the spatial structure was altered in proteins undergoing ubiquitylation, the binding and corresponding catalytic activity would also be changed. This is consistent in our study as well as other reports in which the binding and catalytic activity compromised the largest share of the category of molecular function using GO annotation (2830). In the functional clustering analysis of ubiquitylome after perifosine treatment, proteasome and ribosome were highly enriched (Figure 3A,B).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…As the spatial structure was altered in proteins undergoing ubiquitylation, the binding and corresponding catalytic activity would also be changed. This is consistent in our study as well as other reports in which the binding and catalytic activity compromised the largest share of the category of molecular function using GO annotation (2830). In the functional clustering analysis of ubiquitylome after perifosine treatment, proteasome and ribosome were highly enriched (Figure 3A,B).…”
Section: Discussionsupporting
confidence: 94%
“…In the motif analysis, we found the sequence of negative-charged amino acids [glutamic acid (E) and aspartic acid (D)] frequently emerged in the positions near Kub (Figure 1). This result was consistent with previous reports of ubiquitylome analysis in mammals (28,29) as well as in plants (30), indicating that it might be a general feature in lysine ubiquitination. As the spatial structure was altered in proteins undergoing ubiquitylation, the binding and corresponding catalytic activity would also be changed.…”
Section: Discussionsupporting
confidence: 93%
“…It was suggested that HMGA2 promotes Dvl2 expression, leading to enhanced activation of the Wnt/β-catenin pathway [ 188 ]. The inhibitory effect of the let-7g on the expression of the HMGA2 was demonstrated in a 5-FU-resistant human hepatoma cell line and it also reduced cyclin A expression, which is the key regulator of S phase and mitosis [ 189 ]. Additionally, our previous study showed that HMGA2 silencing using mature specific siRNAs sensitizes breast cancer cells to paclitaxel [ 190 ].…”
Section: Hmga2 Increase Cancer Drug Resistancementioning
confidence: 99%
“…From a study by Yang et al, it was also evident that overexpression of HMGA2 induces autophagy in neurofibromas through its interaction with Musashi-2 promoter region [ 32 ]. Later studies have linked HMGA2 to autophagy, where HMGA2 was identified to mediate autophagy by the carcinogen Cr (VI) [ 33 ], and HMGA2 overexpression was observed to suppress gefitinib resistance in NSCLC cells by inhibiting autophagy [ 34 ]. Additionally, a recent study by Jia et al showed that HMGA2 overexpression increased proliferation, migration and invasion of glioblastoma cells through activation of Wnt/β-catenin pathway and inhibition of autophagy [ 35 ].…”
Section: Discussionmentioning
confidence: 99%